Acinetobacter baumannii K20 and K21 capsular polysaccharide structures establish roles for UDP-glucose dehydrogenase Ugd2, pyruvyl transferase Ptr2 and two glycosyltransferases. (9th August 2018) - Kasimova, Anastasiya A; Kenyon, Johanna J; Arbatsky, Nikolay P; Shashkov, Alexander S; Popova, Anastasiya V; Shneider, Mikhail M; Knirel, Yuriy A; Hall, Ruth M
Abstract: Infections caused by Acinetobacter baumannii isolates from the major global clones, GC1 and GC2, are difficult to treat with antibiotics, and phage therapy, which requires extensive knowledge of the variation in the surface polysaccharides, is an option under consideration. The gene clusters directing the synthesis of capsular polysaccharide (CPS) in A. baumannii GC1 isolate A388 and GC2 isolate G21 differ by a single glycosyltransferase ( gtr ) gene. They include genes encoding a novel UDP-glucose dehydrogenase (Ugd2) and a putative pyruvyl transferase (Ptr2). The composition and structures of the linear K20 and K21 tetrasaccharide repeats (K units) of the CPSs isolated from A338 and G21, respectively, were established by sugar analyses and Smith degradation along with 1D and 2D 1 H and 13 C NMR spectroscopy. The K20 and K21 CPSs are the first known to include Glc p A produced by Ugd2 and d -galactose with an ( R )-configured 4, 6-pyruvic acid acetal added by Prt2. The first sugar in the tetrasaccharide K units is 2-acetamido-4-amino-2, 4, 6-trideoxy-d- glucose (d -Qui p NAc4N) that carries a 4-N-[( S )-3-hydroxybutanoyl] group in some K units and a 4-N-acetyl group in the others. Accordingly, K unit polymerases WzyK20 and WzyK21 form a β-d -Qui p NAc4NR-(1→2)-d -Gal p bond. The K20 and K21 units differ only in the configuration of the glycosidic linkages of d -Glc p NAc allowing the unique inverting glycosyltransferases Gtr43 and the retaining glycosyltransferase Gtr45 to be assigned to the formation of the β-d -Glc p NAc-(1→4)-d -Glc p A and α-d -Glc p NAc-(1→4)-d -Glc p A linkages, respectively.